Pengaruh Kompetensi Achievement And Action Dan Kompetensi Helping And Human Service Terhadap Kinerja Karyawan F&B Departement Di Hotel Mutiara Bandung - Rima, Ayu; Turgarini, Dewi; Meilani, Sylvia (Gastronomy Tourism Journal, 2015)
The purpose of this research is to measure the influence of Achievement andAction Competence Variabel (X1) as well as Helping and Human Service Competence Variabel (X2) on Performance (Y). Based on survey results revealed that the level of Achivement and Action Competentence to performance is equal to 79%, while the level of Helping and Human service Competenceis 19%. Simultaneously, Achivement and Action Compentence as well as helping and Human Service affect the performance on FB Departement employee significantly.